PERILAKU ANAK TERHADAP PENGGUNAAN FASILITAS BERMAIN DI TAMAN BUNGKUL SURABAYA - Maharani, Rizka Tiara; Harmunisa, Yusvika Ratri; Perdana, Adithea Syaputra (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2023)
Abstract: Bungkul Park, located in Surabaya, Indonesia, is a prominent urban park distinguished by its captivating architectural style. The park is frequently used by youngsters, who are drawn to its setting and amenities that have been purposefully tailored to facilitate play and social interaction. However, further investigation is required to examine the behavioral patterns exhibited by children during their visits to Surabaya, as well as the safety measures implemented in various recreational facilities. The objective of this study is to gain insight into the behavioral patterns exhibited by youngsters in Taman Bungkul. The employed research methodology entails a qualitative approach, incorporating observation, behavior mapping, and questionnaires as data collection tools. The target population for this study comprises children aged 2-13 years who frequent Bungkul Park. The analysis of the existing text data will be conducted using the JMP analysis program. Researchers employ observational methods to examine the behavior of children, including activities such as running, playing, and engaging with architectural features such as benches, parks, and other recreational spaces. The behavior of the child is subsequently delineated using behavior mapping. In addition, the researchers employed questionnaires consisting of inquiries to obtain a more profound understanding of children's views and preferences about architectural designs within park settings. The findings of this study suggest that Bungkul Park exhibits considerable appeal as a recreational space for children. However, it is imperative to address some aspects, particularly pertaining to the safety of children, in order to enhance their overall experience. The behavior of children is subject to notable influences from both gender and age, although the magnitude of these influences may not be very substantial. The implications of the study's findings hold significance for urban garden designers and architects, as they pertain to the creation of spaces that effectively engage children and align with their preferences.Keyword: architecture; child behavior; city park; SurabayaAbstrak: Taman Bungkul merupakan salah satu taman kota di Surabaya, Indonesia, dengan desain arsitektur yang menarik. Taman ini sering dikunjungi oleh anak-anak dimana lingkungan dan fasilitas yang ada telah dirancang khusus untuk bermain dan berinteraksi. Namun, perlu dikaji mengenai bagaimana pola perilaku anak saat berkunjung di Surabaya serta keamanan yang ada di seluruh fasilitas bermain. Sehingga, tujuan penelitian ini adalah untuk memahami bagaimana anak-anak berperilaku di Taman Bungkul. Metode penelitian yang digunakan adalah metode kualitatif dengan menggunakan observasi, behaviour mapping dan kuisioner terhadap anak-anak berusia 2-13 tahun yang mengunjungi Taman Bungkul. Data text yang ada akan dianalisis dengan menggunakan software analisis JMP. Melalui observasi, peneliti mengamati perilaku anak-anak seperti berlari, bermain, berinteraksi dengan elemen arsitektur seperti bangku, taman, dan area rekreasi lainnya. Perilaku anak tersebut kemudian digambarkan melalui behaviour mapping. Selanjutnya kuisioner yang berupa pertanyaaan digunakan untuk memperoleh wawasan lebih dalam tentang persepsi dan preferensi anak terhadap desain arsitektur di taman. Hasil penelitian ini menunjukan bahwa Taman Bungkul merupakan area bermain yang cukup diminati oleh anak-anak tetapi masih ada beberapa yang harus dibenahi terutama dari segi keamanan untuk anak-anak. Perilaku anak sangat dipengaruhi berdasarkan jenis kelamin dan usia tetapi tidak terlalu signifikan. Temuan dari penelitian ini memiliki implikasi penting bagi perancang taman kota dan arsitek di dalam merancang lingkungan yang merangsang partisipasi anak agar dapat lebih menarik dan sesuai dengan kebutuhan mereka.Kata Kunci: arsitektur, perilaku anak, Surabaya, taman kota.